The Virtual Neurologic Exam: Instructional Videos and Guidance for the COVID-19 Era - Al Hussona, Mariam (Can J Neurol Sci, 2020)
OBJECTIVE: To outline features of the neurologic examination that can be performed virtually through telemedicine platforms (the virtual neurological examination [VNE]), and provide guidance for rapidly pivoting in-person clinical assessments to virtual visits during the COVID-19 pandemic and beyond. METHODS: The full neurologic examination is described with attention to components that can be performed virtually. RESULTS: A screening VNE is outlined that can be performed on a wide variety of patients, along with detailed descriptions of virtual examination maneuvers for specific scenarios (cognitive testing, neuromuscular and movement disorder examinations). CONCLUSIONS: During the COVID-19 pandemic, rapid adoption of virtual medicine will be critical to provide ongoing and timely neurological care. Familiarity and mastery of a VNE will be critical for neurologists, and this article outlines a practical approach to implementation.